Career Development Of The Millenial Generation - Ema Yudiani; PA. Andiena Nindya Putri; Al Halik; Arief Yanto Rukmana; Zamratul Aini (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
With its human resources potential, companies in Indonesia have a challenge managing human resources, especially the millennial generation. Increasing corporate growth and development in Indonesia has a positive impact on society with increased employment opportunities, which will reduce the unemployment rate. One of the efforts to retain employees is that the company should pay attention to the career development of each employee, especially for millennial generation employees who have good performance. There are some issues in the process of career development in the company that are the subject of research, such as the millenial generation employee who cannot develop his career at the company where he works, while the employees feel they have done their job well. Research methods in this research are e-learning methods and interviews, as well as providing questionnaires to research subjects. The research subject in this study is a millennial generation employee at Bank Rakyat Indonesia (BRI). Learning is both a strategy and a solution for an organization or company, as well as for an individual, to adapt and take effective action to create a competitive advantage.